Pharmacokinetic and Efficacy Study of Acyclovir Against Cyprinid Herpesvirus 3 in Cyprinus carpio - Quijano Cardé, Eva Marie; Yazdi, Zeinab; Yun, Susan; Hu, Ruixue; Knych, Heather; Imai, Denise M.; Soto, Esteban (Frontiers in Veterinary Science, 2020)
Cyprinid Herpesvirus 3 (CyHV-3), more commonly known as Koi Herpesvirus (KHV), is a re-emergent virus causing acute systemic infection with high mortality rates in koi fish (Cyprinus carpio). Survivors from outbreaks can become latent carriers, with viral reactivation under stressful conditions and permissible temperatures. No vaccines or treatments are currently available in the United States. Acyclovir has been shown effective in vitro against KHV. This study aimed to evaluate the cytotoxicity of acyclovir and cidofovir to koi fin (KF1) cells, the efficacy of a single antiviral intracoelomic dose in a koi fingerling cohabitation challenge, and the pharmacokinetics of the effective antiviral. Initially, a lactate dehydrogenase release-based assay revealed no significant acyclovir or cidofovir cytotoxicity to KF1 cells for 24 hours at up to 1500 𝜇M. In laboratory-controlled challenges, KHV associated mortalities occurred two weeks post-infection. At this point, fish were treated with an antiviral (10 mg/kg acyclovir or 5 mg/kg cidofovir) or sterile phosphate-buffered solution. Morbidity and mortality were monitored for 30 days. A significant cumulative mortality reduction (p ≤ 0.05), and a 3-day mortality delay were detected in the acyclovir-treated group. Similar viral loads were detected in gills recovered from mortalities throughout the challenge and surviving fish at the end of the challenge regardless of treatment. For pharmacokinetic analysis, blood was collected at various timepoints after acyclovir administration. Liquid chromatography tandem mass spectrometry plasma analysis indicated a 141 𝜇M peak plasma concentration at 0.75 h, a 14 h half-life, and a 0.05 / h elimination rate constant. Histopathology of target tissues detected no evidence of acyclovir toxicity. Results suggest that a single 10 mg/ kg dose of acyclovir administered intracoelomically to koi fingerlings is safe and reduces cumulative mortality during a KHV mortality event. However, multiple doses are probably required for effective treatment of pet fish.